2021
DOI: 10.1002/tox.23412
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation exposure to silver nanoparticles induces hepatic inflammation and oxidative stress, associated with altered renin‐angiotensin system signaling, in Wistar rats

Abstract: Silver nanoparticles (AgNPs) have become increasingly popular in the biomedical field over the last few decades due to its proven antibacterial property. Previous scientific studies have reported that one of the major organs responsible for detoxification of AgNPs is the liver. The liver is also the primary organ responsible for secretion of angiotensinogen (AGT), a key signaling molecule involved in the renin‐angiotensin system (RAS), which plays an important role in maintaining cardiac output and vascular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…Li found that AgNPs, rather than silver ions, induced mitochondrial dynamics disorders, oxidative stress, and mitochondria-dependent hepatocyte apoptosis in mice ( Li et al, 2021 ). Recently scientific studies have demonstrated the hepatotoxic potential of AgNPs, such as histopathological hepatic lesions, oxidative stress, activation of inflammatory signaling, and pathological lipid peroxidation, when administrated in vivo in a dose-dependent manner ( Jia et al, 2017a ; Nayek et al, 2022 ). NAFLD is the leading cause of chronic liver disease worldwide with a 2-fold increase in the past 2 decades and afflicts approximately 30% of the general population and up to 95% of subjects with obesity and diabetes ( Eslam et al, 2018 ; Younossi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li found that AgNPs, rather than silver ions, induced mitochondrial dynamics disorders, oxidative stress, and mitochondria-dependent hepatocyte apoptosis in mice ( Li et al, 2021 ). Recently scientific studies have demonstrated the hepatotoxic potential of AgNPs, such as histopathological hepatic lesions, oxidative stress, activation of inflammatory signaling, and pathological lipid peroxidation, when administrated in vivo in a dose-dependent manner ( Jia et al, 2017a ; Nayek et al, 2022 ). NAFLD is the leading cause of chronic liver disease worldwide with a 2-fold increase in the past 2 decades and afflicts approximately 30% of the general population and up to 95% of subjects with obesity and diabetes ( Eslam et al, 2018 ; Younossi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…AgNP-intoxication significantly disturbed liver function, elevated hepatic lipid peroxidation, increased liver DNA damage, and induced biochemical and histological alterations in rats ( Albrahim and Alonazi, 2020 ). Subacute exposure to AgNPs induces hepatic inflammation, macrophage infiltration, oxidative stress, and altered liver renin-angiotensin system signaling in Wistar rats ( Nayek et al, 2022 ). Mice intravenously injected with AgNPs had an increased prevalence of hepatocellular necrosis and gall bladder hemorrhage, especially in mice injected with 10 nm AgNPs ( Recordati et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…wnt2bb and mypt1 play important roles in the formation phase of liver progenitor cells. They are essential molecules for liver development in zebrafish [ 32 ]. It was found that the expression level of wnt2bb and mypt1 decreased after exposure to Nano-ZnO, but there was no significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies showed that oxidative stress and inflammation might play a crucial role in inducing multi-organ injury. [13][14][15][16][17][18][19][20] Recent pharmacological studies have revealed anti-apoptotic, antioxidant, and anti-inflammatory properties of Cat. [21][22][23] Moreover, Fu et al insinuated that Cat suppressed inflammation to mitigate acute lung injury in LPS-treated acute lung injury mice.…”
mentioning
confidence: 99%